Experimental study and numerical modelling of woven fabric kenaf fiber composites hybrid adhesively bonded-bolted joints - Lee, Sim Yee (2018)
Couple with natural fiber composite parts, hybrid joints provide better joint strength than using separate joints. There are limited studies on structures response and strength prediction work on hybrid joints that limits its applicability. The aim of present study is to conduct experimental datasets on woven fabric kenaf fiber reinforced polymer (KFRP) and carbon fiber reinforced polymer (CFRP) composite hybrid joints under quasi-static testing and to carry out the strength prediction works subsequently by implementing physically-based traction-separation constitutive law. Testing series investigated includes variation of joint types, normalized W/d = 2 to 5, reinforcing fiber composites, lay-up types, plate thickness and bolt loads. Experimental observations and bearing stress at failures were conducted, the datasets were then used as validation works in FEA modelling. All KFRP hybrid joint series demonstrated net-tension failure mode associated to stress concentration at the vicinity of notch tip. Initially, strength prediction works were attempted by implementing various numerical approaches and fully XFEM techniques was adopted to all series as it provides promising results with better physically representation and less computational time. Good agreements between experimental datasets and predicted bearing stress at failure were found in KFRP hybrid joints with average discrepancy of less than 23%. It was found that combinations of thicker and cross-ply lay-up gives the best prediction of less than 2 % (where experimental datasets and FEA output were given as 201 N/mm2 and 198 N/mm2 respectively) due to better repetitive lay-up with implementation of smeared-out properties. Less significant effects from bolt loads and reinforcing fibers were found for both joint types. It can be concluded that fully XFEM technique able to provide as a unified prediction tools in hybrid joints of most composite materials with reasonable agreements.